1999
DOI: 10.1017/s0263034699172197
|View full text |Cite
|
Sign up to set email alerts
|

Investigations of ion streams emitted from plasma produced with a high-power picosecond laser

Abstract: This work reports on investigations of parameters of ion streams emitted from a plasma produced with a picosecond laser at the power densities ≥1016 W/cm2. Not many papers dealing with such investigations have been published up to now, in spite of the fact that the application of precise corpuscular diagnostics enables better learning of the physical properties of such a plasma. As a result of the investigations carried out, the average and maximum energies of Cu ions were 30 keV and 150 keV, respectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
75
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 75 publications
(91 citation statements)
references
References 0 publications
6
75
0
Order By: Relevance
“…From our experience of relativistic self-focusing (Hora 1975;Jones et al 1982;Häuser et al 1992;Osman et al 1999;, it is necessary to have plasmas of about critical density with a depth of 1 to 2 times the laser beam diameter in vacuum for relativistic self-focusing in front of the irradiated target. We could conclude that the ps laser pulse in the experiment (Badziak et al 1999) could not have produced this necessary plasma for the relativistic shrinking of the beam. At best it can only produce plasma of less depth than one third of the beam diameter in front of the target.…”
Section: Experiments Confirming the Skin Layer Interactionmentioning
confidence: 90%
See 3 more Smart Citations
“…From our experience of relativistic self-focusing (Hora 1975;Jones et al 1982;Häuser et al 1992;Osman et al 1999;, it is necessary to have plasmas of about critical density with a depth of 1 to 2 times the laser beam diameter in vacuum for relativistic self-focusing in front of the irradiated target. We could conclude that the ps laser pulse in the experiment (Badziak et al 1999) could not have produced this necessary plasma for the relativistic shrinking of the beam. At best it can only produce plasma of less depth than one third of the beam diameter in front of the target.…”
Section: Experiments Confirming the Skin Layer Interactionmentioning
confidence: 90%
“…The final result for the maximum ion energy ε trans after relativistic self-focusing (Hora 1975;Jones et al 1982;Häuser et al 1992;Osman et al 1999;, fitting with all the long years of observations (Haseroth et al 1996) with laser pulses longer than 100 ps, was found to be dependent on the laser power P , the ion charge Z and the focused beam Number of (integrated signal) emitted fast ions and thermal ions from a perpendicular irradiated copper target at neodymium glass irradiation for 1.2 ps pulses depending on the laser pulse energy focused to a 30 wavelength diameter beam at the target surface with suppression of a prepulse by 10 8 for a time less then 100 ps before the main pulse arrived. During the last 100 ps the contrast ratio was about 10 4 (Badziak et al 1999(Badziak et al , 2003Hora, Badziak et al 2002a). diameter δ in multiples of the laser vacuum wave length (larger than 0.6) as in the following relation:…”
Section: Experiments Confirming the Skin Layer Interactionmentioning
confidence: 95%
See 2 more Smart Citations
“…The S-LPA mechanism was actually discovered at the end of the nineties [38], but just recently this mechanism has been relatively well understood and proved by both numerical simulations and experiments [19,20,[39][40][41][42].…”
Section: Skin-layer Ponderomotive Accelerationmentioning
confidence: 95%